Science, Technology and Innovation: Concepts, Theory and Policy - Zehra Taşkın; Güleda Doğan (Türk Kütüphaneciliği)
This study is a review of the book entitled “Science, Technology and Innovation: Concepts, Theory and Policy”. In the converging world, the book is an important contribution not only for the field of economy, but also information science which includes information-economy concepts.